Avaliação do processo adsorção do corante laranja BF-GR em casca de soja (Glycine max L) - Aizawa, Juliane Sayuri (2018)
The textile industry consumes around 15% of all Brazilian industrial water, being its highly colored effluent because of the dyes that are not fixed in the fiber and need treatment, the adsorption is a very promising method, however the adsorbents used have a high cost, being economically unviable for the industries, becoming necessary alternative adsorbents. Considering the problem of textile effluent, this work had as objective to employ the in natura and citric acid modified soybean hull as adsorbent of the Orange Reactive BF-GR dye. To characterize the in natura and modified soybean hulls, crude fiber (22.41 and 38%), dry matter (69.08 and 81.49%), ashes (4.22 and 1.95%), Infrared with Fourrier Transform (IRFT) with appearance of bands of the OH bond and higher intensity of bands of the CO bond in the modified soybean hull compared to the normal soybean hulls. In the adsorption tests, kinetic tests were performed, where adjustments were better made to the pseudo-second order model at conditions with a temperature of 25 ± 2 ºC, pH equal to 3, with initial concentrations of 20 and 40 mg L-1 of dye, the isotherm tests (for the in natura soybean hull the Langmuir model was better adjusted and the modified soybean hull was Freundlich) using different initial concentrations of adsorbate (10 to 50 mg L-1), the thermodinamic, Gibbs free energy presented negative values, with enthalpy above 40 kJ mol-1, positive entropy and high activation energy, for both in natura and modified soybean hulls. With maximum removal of 5.66 mg g-1 and 5.55 mg g-1 of the in natura and modified soybean hull, demonstrating that they are excellent adsorbents for the Orange Reactive BF-GR dye, only having a statistical difference between the hull of normal and modified soybean at lower concentrations (20 mg L-1).